Prospective Science Teachers' Information Literacy and Scientific Argumentation Skills in Online Learning During COVID-19 Pandemic - Hidayati, S. N.; Dasna, I. W.; Munzil, M.; Wonorahardjo, S.; Kohar, A. W. (Jurnal Pendidikan IPA Indonesia, 2023)
This study aims to analyze prospective science teachers’ information literacy and scientific argumentation skills and their correlations in online learning during the COVID-19 pandemic. This survey research with a cross-sectional design involved 342 students from a state university in Surabaya. The survey was given online to all respondents with a response rate of 77%, consisting of 23 men and 241 women. The information literacy skill instrument was adapted from the eight indicators of the empowering eight model and declared valid. Indicators include the ability to identify, explore, select, organize, create, present, access input, and use information. The argumentation skills instrument consists of four indicators: the ability to identify claims and their qualifications, identify types of data and their quality, identify reasons and quality, and identify objections and counter-arguments. In contrast to the results of previous studies in this study, prospective teachers’ information literacy obtains an average of 83% in a good category. Based on the correct answers to the four indicators, the argumentation skills used obtained an average score of more than 50% on the less and very poor criteria. Based on the SPSS one-tailed correlation test, a correlation coefficient of 0.103 is obtained with very low criteria. This study concludes that students’ information literacy skills are in line with their argumentation skills but in very little correlation.